2023
DOI: 10.3390/ijms24031815
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies of Artificial Intelligence on In Silico Drug Distribution Prediction

Abstract: Drug distribution is an important process in pharmacokinetics because it has the potential to influence both the amount of medicine reaching the active sites and the effectiveness as well as safety of the drug. The main causes of 90% of drug failures in clinical development are lack of efficacy and uncontrolled toxicity. In recent years, several advances and promising developments in drug distribution property prediction have been achieved, especially in silico, which helped to drastically reduce the time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Tong et al [ 59 ] showed the utility of uncertainty estimations for improving the predictability of deep learning BBB permeability models. An excellent review of classification models using different datasets and different ML and DL algorithms is published by Saxena et al [ 60 ] and Tran et al [ 61 ]. These qualitative classification models are helpful for quick screening of large compound databases at early-stage drug discovery.…”
Section: Bbb Penetration Scoring Schemes For Predicting Brain Penetra...mentioning
confidence: 99%
“…Tong et al [ 59 ] showed the utility of uncertainty estimations for improving the predictability of deep learning BBB permeability models. An excellent review of classification models using different datasets and different ML and DL algorithms is published by Saxena et al [ 60 ] and Tran et al [ 61 ]. These qualitative classification models are helpful for quick screening of large compound databases at early-stage drug discovery.…”
Section: Bbb Penetration Scoring Schemes For Predicting Brain Penetra...mentioning
confidence: 99%
“…AI-powered decision support systems unite the information on patients' demographics, clinical histories and treatment outcomes and make diagnosticians insightsbased decisions, which consequently lead to better treatment outcomes in the management of tinnitus. [17] And they (Van Tran et al, 2023) go on a pathway of the most recent research of AI in in silico drug distribution prediction. Such researchers emphasize the potential utilization of AI-based predictive modeling techniques for improve drug distribution procedures.…”
Section: Iirelated Workmentioning
confidence: 99%
“…However, we only focus on highlighting 11 properties that have been of interest to many AI-based ADMET researchers, including the logarithm of the octanol–water partition coefficient (log P), the logarithm of pH-dependent distribution coefficient (log D), the logarithm of the aqueous solubility (log S), p K a , human oral bioavailability (HOB), human intestinal absorption (HIA), Caco-2 cell permeability, P-glycoprotein (P-gp) inhibitor and substrate, parallel artificial membrane permeability assay (PAMPA), and Madin-Darby Canine Kidney Cells (MDCK) permeability. Interested readers can refer to other useful ADMET property reviews. …”
Section: Progress On Ai-based Drug Absorption Predictionmentioning
confidence: 99%